Introduction. Media, culture and social change: Interdisciplinary perspectives - Castro Pérez, Raúl (2019)
This volume, "Media, culture and social change: interdisciplinary perspectives", offers, in short, a preliminary and no less thorough approach - due to its diversity of themes and approaches - to the study of one of the main emerging fields in the discipline: the multimodal anthropologies of the media. The volume also attempts to respond to the challenge of showing the new social formations constituted in interactivity with the new media platforms that are promoting not only the ethnographic study of significant practices on platforms such as Facebook, Instagram or YouTube as places of socialization and cultural creation, but also the use of its resources as tools for public projection of academic production. The latter is an aspiration that we hope will also fulfill this set of studies. Access to them via digital systems that you, the user of these texts, are having, allows us to consider it as such. Surely an upcoming thematic volume like this should reflect on it.